PENGEMBANGAN METODE PENENTUAN ANILINA DALAM BAHAN BAKU NATRIUM SIKLAMAT SECARA SPEKTROFOTOMETRI ULTRAVIOLET-SINAR TAMPAK - Yuliantini, Anne
Aniline is an impurity which could be present in sodium cyclamate. Due to its toxicities, the concentration of this impurity in sodium cyclamte is according to The European Pharmacopoeia 6.0, limited to a maximum level of 1µg/g. This Pharmacopoeia describes the determination of aniline applying gas chromatography method. As alternative to that compendia I method, this research aims to establish an analytical method for determination of aniline by means of UV/VIS-spectrometry. Aniline was extracted from aqueous solution of sodium cyclamate using toluene under adjusted pH value of 12.4 and then re-extracted from that organic phase using a 1 N hydrochloric acid solution. Aniline dissolved as hydrochloric acid salt was reacted with nitrous acid, which was produced in situ from sodium nitrite and hidrochloric acid, to form a diazonium salt. To remove excess nitrous acid, urea was added to reaction mixture. The diazonium salt was then coupled with N-(1- naphthyDethylenediamine dihydrochloride at adjusted pH value of 1.5 to result in a diazodyes structure. The absorbance of the solution was then measured at 554 nm. This method gave a linear calibration curve in the concentration range of 0.5 to 1.75 iig/mL with a regression equation of y = 0.4303x + 0.039 and r2 = 0.999. The limit of detection and limit of quantification of this method were, statistically calculated, 0.0411 and 0.1371 pg/mL, respectively. The recovery of standard addition of aniline in sodium cyclamate at the concentration levels of 1.0 and 2.0 ng/g were 90.0 and 95.0 %, respectively. The relative standard deviations of all aniline determinations were less than 5%. Based on these results, it was concluded that this method is suitable to be applied as alternative method for determination of aniline in sodium cyclamate.